2021
DOI: 10.1155/2021/2822950
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Inhibits Human Lung Adenocarcinoma by Suppressing MiR-27b and MiR-92a

Abstract: Lung adenocarcinoma (LUAD) is one of the most prevalent malignancies. However, its mechanism and therapeutic strategy remain to be clarified. Mangiferin is a flavonoid derived from the leaves of mango trees of the lacquer family that has many pharmacological and physiological effects. This research aimed to elucidate the biological effect of mangiferin in LUAD cell lines and clarify the in vitro mechanism of mangiferin. Mangiferin was shown to significantly restrain the proliferation of LUAD cells (A549, H1299… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It had been previously reported that mangiferin displayed anticancer effects on A549 cells through various mechanisms, such as induction of apoptosis and reduction of miR-92a and miR-27b expression. 26,42 Our studies demonstrated that mangiferin was able to inhibit cell migration and invasion on A549 cells without cytotoxicity, however, the migration of cancer cells involved multiple mechanistic pathways, the precise molecular mechanism of cell migration inhibition should be further studied.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It had been previously reported that mangiferin displayed anticancer effects on A549 cells through various mechanisms, such as induction of apoptosis and reduction of miR-92a and miR-27b expression. 26,42 Our studies demonstrated that mangiferin was able to inhibit cell migration and invasion on A549 cells without cytotoxicity, however, the migration of cancer cells involved multiple mechanistic pathways, the precise molecular mechanism of cell migration inhibition should be further studied.…”
Section: Discussionmentioning
confidence: 92%
“…26 Another report indicated that mangiferin likely regulated proliferation and apoptosis in lung cancer LUAD cells by reducing the expression levels of miR-92a and miR-27b. 42 Cancer cell migration is one of the important steps in cancer spread and invasion. Inhibitions of A549 cells migration have been widely reported for evaluation of lung carcinogenesis and cancer cells growth.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, mangiferin. exhibits anti−tumor properties in A549 xenograft mice in vivo, and may negatively regulate the expression of miR-92a and miR-27b to influence not only cancerous growth but also the cell cycle progression and apoptosis induction of LUAD cells (34,35). Formononetin inhibits tumor growth by suppression of EGFR-Akt-Mcl-1 axis in non-small cell lung cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Genistein [254] miR-574-3p [255] Psoralidin [256] miR-27a-3p [257], miR-155-5p [258], miR-223-3p [259] ↓ Quinic acid [179] Hesperidin [260] miR-16-5p, miR-34a-5p [261], miR-132-3p [262] Vanillin [263] Zymosan A [264] miR-21-5p [181,182] ↓ Dieckol [265] Mangiferin [11] miR-15b-5p [266], miR-27b-3p, miR-92a-3p [267] Eckol [268] Matrine [269] miR-22-3p [177], miR-19b-3p [270] Phloroglucinol [271] miR-21-5p [181,182] ↓…”
Section: Natural-product-regulated Mirnasmentioning
confidence: 99%
“…Mangiferin (2 mg/kg), a Mangifera indica-derived glucosylxanthone, enhanced the survival of 10 Gy irradiated mice [11]. Mangiferin suppressed proliferation and triggered the apoptosis of glioma and lung cancer cells by upregulating miR-15b-5p [266] and downregulating miR-27b-3p and miR-92a-3p [267] (Table 1), respectively. Matrine (30 mg/kg), a Sophora-plant-derived alkaloid, increased the survival of 7 Gy irradiated rats [269].…”
Section: Functions Of Radioprotective Natural Products In Anticancer ...mentioning
confidence: 99%